Conceptualising 'Learning' in Applied Linguistics 2010
DOI: 10.1057/9780230289772_7
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Changes and Methodological Challenges: On Language and Learning from a Conversation Analytic Perspective on SLA

Abstract: The last two decades have been witness to the increasing influence, across several disciplines in the human sciences, of research that challenges established conceptions of learning and of language. Within socioculturally and socio-interactionally oriented research, attention has shifted away from an understanding of language learning/acquisition as an intra-psychological, cognitive process enclosed in the mind of the individual, toward a concern with how learning is anchored and configured in and through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 0 publications
2
55
0
11
Order By: Relevance
“…He, 2004;Markee & Kasper, 2004;Mondada & Pekarek, 2004;Kasper, 2006;Pekarek Doehler, 2010;Barraja-Rohan, 2011;Seedhouse, 2013; and more recently CA has begun to be applied in online language learning environments (González-Lloret, 2015). González-Lloret points out that this is a growing area of research, an assertion that is supported by the number of studies in online learning environments that depart from a CA perspective (cf.…”
Section: Methodsmentioning
confidence: 80%
“…He, 2004;Markee & Kasper, 2004;Mondada & Pekarek, 2004;Kasper, 2006;Pekarek Doehler, 2010;Barraja-Rohan, 2011;Seedhouse, 2013; and more recently CA has begun to be applied in online language learning environments (González-Lloret, 2015). González-Lloret points out that this is a growing area of research, an assertion that is supported by the number of studies in online learning environments that depart from a CA perspective (cf.…”
Section: Methodsmentioning
confidence: 80%
“…In line with other authors (Brouwer &Wagner, 2007;Doehler, 2010;Moore, 2014) learning in this study is conceptualized as a dynamic social process, situated in communities of practice, and which requires a longitudinal perspective. Opportunities for learning in this study are identified as interactional phenomena which focus on content and linguistic aspects of a specific learning object during the social process of the class generation and application of an assessment instrument.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…Özellikle KÇ'nin sistematik, kanıta dayalı analitik bulguları, sınıf içi etkileşimin farklı mikro bağlamlarını, bu bağlamların çeşitli etkileşimsel kaynaklarını tespit etmiş (Seedhouse, 2004) ve bu kaynakların uygun kullanımı ile bireylerin etkileşimsel yetilerinin zamanla geliştiğine kanıt getirmiştir (Pekarek Doehler, 2010).…”
Section: Yabancı Dil Eğitimi Ve Sınıf İçi Etkileşimunclassified